Charaudeau, Patric. Les médias et l’information: l’impossible transparence du discours. 2nd. éd. rev et augm. - Longo, Brunella (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
In this scholarly review of the last edition of "Les médias et l’information" Brunella Longo tracks back the evolution of Patric Charadeau’s theory of media communication and suggests the work should be considered a companion of other fundamental handbooks and essays about media and information literacy. The analysis addresses aspects interesting both media and cultural studies and practitioners practices.